Genome Variability for the Development of Coronary Heart Disease in Type 2 Diabetes Mellitus: A Bibliometric Analysis - Bekenova NB; Vochshenkova TA; Zhylkybekova A; Ablakimova N; Mussin NM; Albayev RK; Kaliyev AA; Tamadon A (Journal of Multidisciplinary Healthcare)
Nazira B Bekenova,1,* Tamara A Vochshenkova,1,* Aliya Zhylkybekova,2 Nurgul Ablakimova,3 Nadiar M Mussin,4 Rustam K Albayev,1 Asset A Kaliyev,4 Amin Tamadon1,5,6 1Gerontology Center, Medical Center of the President’s Affairs Administration of the Republic of Kazakhstan, Astana, Kazakhstan; 2Department of Evidence-Based Medicine and Scientific Management, West Kazakhstan Marat Ospanov Medical University, Aktobe, Kazakhstan; 3Department of Pharmacology, West Kazakhstan Marat Ospanov Medical University, Aktobe, Kazakhstan; 4General Surgery, West Kazakhstan Marat Ospanov Medical University, Aktobe, Kazakhstan; 5Department for Natural Sciences, West Kazakhstan Marat Ospanov Medical University, Aktobe, Kazakhstan; 6PerciaVista R&D Co, Shiraz, Iran*These authors contributed equally to this workCorrespondence: Amin Tamadon; Aliya Zhylkybekova, Email amintamaddon@yahoo.com; zhylkybekovaa@gmail.comIntroduction: Cardiovascular diseases (CVDs) stand as the foremost global cause of mortality, accounting for 32% of total deaths in 2019, with 85% attributed to heart attacks and strokes. Individuals with Type 2 Diabetes Mellitus (T2DM) exhibit an elevated susceptibility to coronary heart disease (CHD). In numerous studies, it has been established that genetic polymorphism of genes influences the onset, progression, and complications of coronary heart disease (CHD) and type 2 diabetes mellitus (T2DM). The aims of this study are to employ bibliometric analysis methods for mapping the array of research on genome variability concerning the development of coronary heart disease in individuals with type 2 diabetes mellitus.Methods: We derived the data from the Web of Science (WoS) Core Collection database and Scopus on January 6, 2023. All publications from 1987 to 2023 are exported in plain text format for WoS-CC and BibTeX format for Scopus, containing bibliographic information, keywords, and citation information. RStudio v.4.1.2 software (RStudio, PBC, Boston, MA, USA) was used for conducting bibliometric analysis.Results: Our analysis of 241 articles published between 1987 and 2023 revealed a consistent increase in research output, especially after 2004, highlighting a growing academic focus on genome variability’s role in coronary heart disease (CHD) development among Type 2 Diabetes Mellitus (T2DM) patients. Key contributing journals include The Lancet and Nature Genetics, indicating high-impact interest in this domain. The United States leads in research productivity and collaboration, with China also emerging as a notable contributor in recent years. Prominent authors such as S. Humphries have significantly shaped the field, contributing to a cumulative knowledge base that underscores the role of genetic factors in CHD among T2DM patients.Discussion: Our findings underscore the value of bibliometric studies in guiding future research directions. This increasing scholarly attention to genome variability in CHD and T2DM may encourage deeper investigation into specific genetic polymorphisms and their mechanistic roles in disease progression. Additionally, these insights can help prioritize collaboration across leading research hubs and potentially drive innovation in therapeutic interventions targeting genetic risk factors in CHD and T2DM. Future research could build on these trends by focusing on comparative studies across populations, advancing precision medicine approaches for at-risk individuals with T2DM.Keywords: Genome Variability, Coronary Heart Disease, Type 2 Diabetes Mellitus, Bibliometric Analysis, Research Hotspots